Associations among Dietary Zinc Intakes and Biomarkers of Zinc Status before and after a Zinc Supplementation Program in Guatemalan Schoolchildren. Issue 2 (June 2013) - Bui, Vinh Q.; Marcinkevage, Jessica; Ramakrishnan, Usha; Flores-Ayala, Rafael C.; Ramirez-Zea, Manuel; Villalpando, Salvador; Martorell, Reynaldo; Digirolamo, Ann M.; Stein, Aryeh D.
Background: The associations among dietary zinc intakes and biomarkers of zinc status are unknown in apparently healthy children at high risk for zinc deficiency. Objective: To assess associations among zinc-related parameters in a sample of Guatemalan school-aged children. Methods: We assessed total dietary intakes and biomarkers of zinc status before and after receiving 6 months of zinc supplementation or placebo in 691 Guatemalan schoolchildren aged 6 to 11 years. Most of the children also received zinc-fortified milk from a government program that started shortly after the trial began. We assessed associations between zinc intakes and serum zinc, alkaline phosphatase (ALP), and albumin. Results: At baseline, the prevalence of serum zinc < 65 μg/dL and dietary zinc intake below Estimated Average Requirements (EAR) (< 4 and < 7 mg/day for children < 9 and ≥ 9 years, respectively) were 21.6% and 39.4%, respectively. Pearson correlations between serum zinc concentration and dietary zinc intake, serum ALP, and serum albumin were r = 0.07, 0.15, and 0.07, respectively. At the 6-month follow-up, low serum zinc and low total (diet plus fortified milk) zinc intakes were observed in 1.2% and 0.0% of children in the zinc-supplemented group and 4.0% and 34.1% in the placebo group, respectively. Pearson correlations between serum zinc concentration and total zinc intake, serum ALP, and serum albumin were 0.10, 0.06, and −0.11 in the zinc-supplemented group and −0.04, 0.05, and 0.01 in the placebo group, respectively. Conclusions: Zinc intake was inconsistently associated with markers of serum zinc concentration. Zinc fortification or supplementation attenuated the associations.